26 Medrev: feasibility study of a pharmacy de-prescribing and health psychology intervention to improve care for people with dementia with BPSD in care homes. (20th August 2018) - Maidment, Ian; ,
Abstract : Objectives: 'Behaviour that Challenges' is common in older people with dementia in care homes and traditionally treated with anti-psychotics. Guidelines across the globe have aimed to reduce the use of anti-psychotics in people with dementia and therefore reduce harm. These initiatives have only been partially successful. This submission reports results on a feasibility study (MEDREV) funded by the NIHR. The study combined a medication review by a specialist dementia care pharmacist combined with staff training with the overall objective of limiting the inappropriate use of psychotropics. Method: Care homes were recruited. People meeting the inclusion (dementia diagnosis; medication for behaviour that challenges), or their personal consultee, were approached. A specialist dementia care pharmacist reviewed medication and recommended the de-prescribing of inappropriate psychotropics. Care staff received a 3 hour training session promoting person-centred care and GPs brief training. The primary outcome measure was the Neuropsychiatric Inventory-Nursing Home version (NPI-NH) at 3 months. Other outcomes included quality of life (EQ-5D/DEMQoL), cognition (sMMSE), health economic (CSRI) and prescribed medication. Qualitative interviews explored expectations and experiences. Results: Five care homes and 34 of 108 eligible residents (31.5%) were recruited. Medication reviews were conducted in 29 of the 34 residents recruited and the pharmacist recommended de-prescribing or reviewing a medication in 21 of these. Fifteen (71.4%) of these 21 medications were antidepressants. 57.1% (12 of 21) of recommendations were implemented; although implementation took a mean of 98.4 days. Themes for non-implementation of recommendations will be presented. In total, 164 care staff received training; 142 from the care homes and 22 GP staff. Twenty-one participants (Care Home Managers=5; General Practitioners=3; Nursing Staff=2; Care Staff=11) were interviewed. Conclusions: People with living with dementia continue to be prescribed inappropriate psychotropics for beaviour that challenges and the current policy may simply have shifted prescribing from anti-psychotics to other equally inappropriate psychotropics. We found the study feasible although our approach may need to be modified to improve the uptake of our reviews and reduce the delay in implementation.